Barremian tricolpate pollen from Portugal—New evidence for the age of eudicot-related angiosperms - Julia Gravendyck; François-Nicolas Krencker; James B. Riding; Rute Coimbra; Ulrich Heimhofer (Proceedings of the National Academy of Sciences, 2025)
New evidence on the timing of early angiosperm evolution is presented through the discovery of four well-dated tricolpate pollen grains from the Early Cretaceous midlatitudes. Recovered from nearshore marine sediments in the Lusitanian Basin of Portugal, these fossils significantly expand the pre-Aptian tricolpate pollen record and document a greater number of pre-Aptian tricolpate grains in the midlatitudes than previously recognized. The fossil evidence was obtained through the innovative application of advanced microscopy techniques and was precisely dated through biostratigraphy and strontium isotope stratigraphy on material from the same section. These findings extend the first occurrence of tricolpate pollen to the early late Barremian (~123.0 Ma) in Portugal and possibly worldwide. Our findings provide fossil evidence with minimal dating uncertainty, as both the fossils and their age determination come from the same well-constrained sections, eliminating the need for cross-correlation. This establishes the most reliable age for the first occurrence of tricolpate pollen, unequivocally linked to the eudicot clade—an early derived lineage within angiosperms. These fossils serve as a robust calibration point for phylogenetic studies. Additionally, our study emphasizes the importance of methodological advancements in refining the fossil plant record. The newly applied fluorescence screening method when adapted also in future research could further enhance the detection of rare fossils, offering insights into the diversification of angiosperms.